Poétique du Désert dans ce Que le Mirage Doit À L’oasis de Yasmina Khadra: La Prosopopée au Service de L’imaginaire Spatial - Missaoui, Samiha; Belgacem, Belarbi (المركز الجامعي الونشريسي تيسمسيلت - مخبر الدراسات النقدية والأدبية المعاصرة, 2022)
The present article focuses on the poetic representation of the desert in Yasmina Khadra’s What the mirage owes to the oasis, it examinesparticularly the way in which the author links prosopopoeia to the spatial imaginary to evoke the memories that marked his life in the desert. This study will be an attempt to answer the following questions: How is the desert depicted in the romantic universe of Yasmina Khadra? Why does he use prosopopoeia to recount it? And how does it play the role of a space of nostalgia and memory? It will be shown at the end that its poetic in Yasmina Khadra’s work lies in this stylistic process which serves as a support to express his nostalgia for his native land.
Keywords: شعر الصحراء -- التمثيل الشعري -- خضرة، ياسمينة